Karakteristik Sensori Dan Kimia Selai Lembaran Dari Kappaphycus alvarezii Dan Sonneratia caseolaris - Ramadani, Andi; Cahyani, Reni Tri (Jambura Fish Processing Journal, 2025)
Sheet jam is an innovation from spreadable jam products, which generally come in paste form. The sheet jam has a compact texture and is not sticky, making it practical to serve. Kappaphycus alvarezii and Sonneratia caseolaris can be used as raw materials to make nutritious, practical, and preferred sheet jam products. This research used experimental design with six treatments including P1 (100:0), P2 (90:10), P3 (80:20), P4 (70:30), P5 (60:40), and P6 (50:50). This research aimed to determine sheet jam's sensory and chemical characteristics from K. alvarezii and S. caseolaris. Sensory test data was analyzed statistically using Kruskal Wallis. The best treatment was determined based on the average sensory value, and then the yield, total sugar, crude fiber content and vitamin C were determined. The results of the sensory statistical test for sheet jam showed no significant differences between treatments (sig 0.05). The best treatment is sheet jam in a ratio of 70:30. The yield, total sugar, crude fiber and vitamin C of the best-treated sheet jam were 60%, 32.12%, 7.08%, and 8.8 mg/100 g, respectively.